Optimising Growing Media Composition and Seed Selection Strategies For the Conversation of the Endangered Sandalwood (Santalum album Linn.) - Blolok, Agustina Sumarni Ciputri; Seran, Wilhelmina; Mau, Astin Elise; Soimin, Muhamad (Forestry Department, University of Muhammadiyah Makassar, 2024)
Overexploitation and insufficient conservation efforts have classified Sandalwood (Santalum album Linn.), an economically and ecologically significant species, as endangered. This study investigates the effects of seed size and growing media composition on the germination performance and growth of sandalwood seedlings, aiming to optimise seed selection and media composition strategies for its conservation. We employed a completely randomised design (CRD) experiment, which included three seed size categories (small, medium, and control) and three media compositions: soil and sand alone, soil and sand with chicken manure, and soil and sand with cow manure. Results revealed that the combination of medium-sized seeds and chicken manure (A2B1) yielded the highest fresh weight (0.31 g), while small seeds combined with chicken manure (A1B1) achieved the highest germination speed index (0.63%/day), germination value (0.07%/day), and dry weight (0.07 g). We identified chicken manure as the most effective organic amendment, enhancing soil structure, microbial activity, and nutrient availability. In contrast, cow manure exhibited slower nutrient release, and soil and sand alone hindered root development due to compact soil properties. These findings underscore the importance of nutrient-rich organic amendments and optimal seed selection in enhancing sandalwood germination and growth. This study provides actionable insights for sustainable sandalwood cultivation and conservation efforts. Further research should focus on field trials under variable environmental conditions to validate these strategies on a larger scale.